Efficiency and Stock Performance of Banks in Transition Countries: Is There A Relationship? - Vardar, Gülin (International Journal of Economics and Financial Issues, 2013)
The study investigates the link between the cost and profit efficiency scores of the banks in the Central and Eastern European Countries as well as Turkey along with their stock price performance to determine whether the efficiency scores are priced accordingly in bank stocks. Changes in efficiency scores of banks, obtained from Stochastic Frontier Analysis (SFA) model, are regressed against their stock price performance by applying fixed effects panel regression technique. Empirical results indicate that changes in profit efficiency estimates have a positive and significant impact on stock returns; however, a significant but negative relationship is found between changes in cost efficiency and stock returns. Keywords: Central and Eastern European Banking; SFA; Efficiency; Stock returns JEL Classifications: G21